Characterization of tribological materials - Glaeser, William A.; Brundle, C. Richard (Materials characterization series, 2012)
Tribology is a discipline concerned with contacting surfaces. This book shows how surface analytical techniques can be used together with the knowledge of basic principles of tribology to help understand failure processes. For instance, Chapter 8 shows how precision ball bearings and their critical lubrication requirements require knowledge of lubricant behavior of very thin films and surface reaction (boundary lubrication) for reliable performance. Thus if a bearing material is altered, it may be necessary to determine its effect on surface chemistry of lubricants. Surface analysis, including wear scar analysis, can be factored into test programs as a supplemental component or as an integral part of the set up.